Optimization of baffle’s height in an asymmetric twin-screw extruder using the response surface model - Yu Huiwen; Jie Xuzhang; Dong Tianwen; Xu Baiping (e-Polymers)
Dispersive mixing is an important indicator for conventional co-rotating twin-screw extruders. In this work, a new asymmetric twin-screw extruder was developed to improve dispersive mixing. An aqueous solution of sodium carboxymethyl cellulose (CMC-Na) was employed as a matrix fluid, and the red oil-based ink was used as a tracer. A response surface model was constructed to predict the average diameter of droplets in terms of the feed rate, screw speed, and baffle height, and then the corresponding optimal solutions were obtained. Visualization experiments indicated that the gap regions between the screw and the barrel are mainly responsible for the tracers’ breakup. Particle image velocimetry experiments further confirmed that high velocity appeared in these gap regions and resulted in high shear rates, especially for a baffle height of 15.5 mm, where the linked regions of high velocity turned up.